Groundwater pollution, aquifer recharge and vulnerability - Robins, N. S. (The Geological Society / USA, 1998)
Contents: The key to groundwater pollution and aquifer Vulnerability; Groundwater recharge and pollution vulnerability of british aquifers a critical overview; Identification of the source and fate of nitrate contamination of the Jersey bedrock aquifer stable nitrogen isotopes; The bristish nuclear fuels drigg low-level site characterization programme